THE POVERTY AND STRUGGLE OF FRANK MC COURT IN ANGELA’S ASHES - Ardhinie, Eka (Journal of Language and Literature, 2020)
One of the literary works is novel. In novel we can find many kinds of characterization. The researcher chooses this novel as the data source because the novel is good to be analyzed about the struggle of human life. It will be a great inspiration and motivation to people who was born in poverty. So, this research aims to find out the characteristics of poverty of Frank McCourt by using a sociological approach and to describe the indicators of poverty as a social problem. The character starts from the child until frank McCourt to be succeed to face the obstacles in poverty. Besides that, the writer wants to know the struggles of Frank McCourt’s life and how he can survive in poverty as a child. As a result, the reader can get the spirit of Frank McCourt’s struggle and about his thought in many kinds character. This research used qualitative method in analyzing the data. The data was collected from a novel of Frank McCourt “Angela’s Ashes” and in the form of quotation from novel that related to Frank McCourt’s character. The result of this research is the characteristics of poverty of Frank McCourt influenced by charity, health, government, justice institution, Limerick community, family, ethnocentrism, and employment office. There are also some indicators of poverty that show the struggle of Frank McCourt to survive in poverty, including: struggle in starving, in the bad situation that makes his father becomes alcoholic and her mother becomes a beggar, poor clothing and housing, and suffers from ill health.